Effect of Ferritic - Martensitic Constituent on Mechanical Property and Corrosion Behaviour of Medium Carbon Dual Phase (DP) Steel - Radhiyah, Abd Aziz; Maisalsadila, Ismail (Scholars Middle East Publisher, 2018)
This investigation was carried out to study the effect ferritic-martensitic constituent on mechanical property and corrosion behaviour of medium carbon DP steel. Several stages of heat treatment were applied on the as-received medium carbon steel which composed of lamellarizing, quenching and tempering process. As-received medium carbon steel was assigned as a reference sample for comparison analysis. Mechanical property was evaluated using Vickers hardness to examine the effect of changing the ferritic-martensitic constituent of the medium carbon steel. Besides, the effect of this constituent on the corrosive behaviour of the medium carbon DP steel was investigated using 1 M hydrochloric acid solution.